Revolution to revolution Jamāʻat-e-Islāmī in the politics of Pakistan - Moten, A. Rashid (Islamic Book Trust in Association with International Islamic University of Malaysia, 2002)
Studies dealing with Islam and politics focus largely upon the impact of Islam on political institutions in the Muslim world. This study reverses the sequence and evaluates the consequences of "politicizing" an Islamic movement. It pinpoints various milestones in the transformation of the Jama'at-e-Islami of Pakistan from a quietist, revivalist organization to an active political party and a mass revolutionary movement. It analyzes the relationship between the elite structure and the transformation of the Jama'at and enquires into the value and validity of this transformation and assesses its impact upon the organization and upon the society as a whole. The book will be of interest to scholars and activists of Islamic political movements and to those concerned with the teaching and learning of Islamic political thought and institutions.